Arab Spring: A Case Study of Egyptian Revolution 2011 - Shinta Puspitasari (Andalas Journal of International Studies (AJIS), 2017)
Egyptian Revolution, also known as Arab Spring or Arab Uprising, was a shock for international community because Egypt has been seen as one of the strongest military state in North Africa region. Experts and observers even suggested that this revolution is the biggest event since the Cold War. No one ever saw this coming; yet, the Revolution happened, and it succeeded to topple President Hosni Mubarak from power. Indeed, prior to the revolution, there are factors that became the preliminary incidents as well as problems that led to the revolution, and most of these factors came from within the country. Nevertheless, this revolution has given idea to other states with repressive regime in the North Africa region, which started the ‘domino effect’ in Middle East and North Africa region. As for Egyptians, though successfullnes of the revolution brought positive outcome for them, the negative result also followed as well as responses from international community. The objective of this paper is to examine the Egyptian Revolution that led to the end of Hosni Mubarak regime. Keywords: Arab Spring; Egyptian Revolution; President Hosni Mubarak; ‘domino effect’; Middle East and North Africa region.